Heterologous expression of cannabidiolic acid synthase in a microbial host for cannabinoid production - Toh, Wing Loon (2019)
Renewed interest in the pharmacological applications of Phytocannabinoids from Cannabis sativa (C. sativa) has created a need for an efficient and scalable biomanufacturing platform to replace resource intensive and largely illegal agricultural approaches. Despite success in reproducing the cannabinoid biosynthetic pathway in various Eukaryotic hosts, Prokaryotic hosts with higher space time yields have been ignored as a suitable alternative. In this study, we attempted to re-engineer the cannabinoid biosynthetic pathway of C. Sativa for optimized prokaryotic heterologous expression. Utilizing ROSETTA overexpression strain E. coli as a host, heterologous protein expression of terminal enzyme cannabidiol synthase (CBDAS) was achieved and optimized. Despite successful expression in harvested total protein fractions CBDAS was not soluble and active. Consequently, fusion with several solubility tags such as glycosylation protein ApNGT, expression reporter mCherry and periplasmic protein DsbA was attempted. The ApNGT CBDAS fusion managed to be expressed was not soluble. DsbA CBDAS appears to have yielded some success in obtaining a soluble protein but further verification is required. Fusion with expression reporter mCherry produced a soluble, and correctly folded mCherry protein but appeared to show degradation of CBDAS despite a correctly constructed plasmid. Lastly, we created a fusion protein NphB CBDAS with dual functions as a substitute for Cannabigerolic Acid Synthase (CBGAS) and a solubility enhancement tag. However, NphB CBDAS remained insoluble despite successful expression in ROSETTA E. coli.